Does Religiosity Matter?: Explaining Right-Wing Extremist Attitudes and the Vote for the Alternative for Germany (AfD) - Huber, Stefan (Religion and society in Central and Eastern Europe, 2019)
In recent years, an intensive scientific discourse has developed on the reasons for the rise of right-wing populist movements and parties throughout Europe. In the German debate, religion and religiosity play only a minor role, whereas the economic deprivation theory is part of many quantitative studies. Against this background, we discuss reasons for right-wing extremist views and for the vote for the German right-wing populist party Alternative für Deutschland (AfD). To explain the role of religiosity in this context, we use Theodor Adorno’s arguments and differentiations within the concept of "The Authoritarian Personality" (Adorno et al. 1950). By analyzing data of the International Social Survey Programme (ISSP subsample within the German General Social Survey ALLBUS 2018 (n=1629), we find that, in the highly secularized region of East Germany, commitment to church is negatively correlated both with right-wing extremist attitudes and the vote for AfD. We assume that this has to do with the Christian doctrine of charity and tolerance as well as with the political position of the church, especially in East Germany. This tolerance reflects Adorno’s type of the "radical Christian," which is characterized by an intrinsic religious motivation. Our data also reveals that a belief in supernatural powers is positively correlated with right-wing extremist attitudes, which reflects Adorno’s type of a "superstitious person," which is characterized by weak ego and an ethnocentric worldview. Our findings underline the necessity of opening the black box of religiosity by differentiating the religious factor.